Abnormal magnetic properties of MnBi thin film synthesized by MBE. (15th November 2017) - Hu, Ping; Wu, Shuxiang; Wang, Gaili; Li, Dan; Zhou, Wenqi; Li, Hongwei; Li, Shuwei
Abstract: MnBi has attracted much attention due to its unusual magnetic properties. It has the potential as an alternative to the permanent magnets containing rare-earth elements. In this paper, the MnBi thin film was grown by plasma-assisted molecular beam epitaxial technique. The as-grown film shows ferromagnetic property and an anomalous magnetization dependence on temperature. The X-ray photoelectron spectrum reveals that there are regular and interstitial sites Mn atoms with two bonding states. The observed decrease of magnetization at ∼230 K would be ascribed to the movements of Mn atoms to the interstitial sites leaving behind Mn vacancies. Also at ∼90 K, it exhibits a spin reorientation due to the magnetization change from c -axis to ab -plane which is related to the abnormal temperature dependence of the lattice parameters.